Methodology for teaching combat techniques to students of educational organisations of the ministry of internal affairs of Russia - Sapunov, A.S.; Tretyakova, N.V.; Gayl, V.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to substantiate the scientific and methodological aspects of training Russian Ministry of Internal Affairs cadets in the tactics of using physical force and combat techniques in conditions close to operational and service activities. Methods and structure of the study. The bibliometrics method was used to analyze scientific and methodological literature; a retrospective analysis of experience and methods of forming combat techniques of wrestling, as well as the study of normative legal acts and teaching aids; synthesis of the information obtained to improve existing methods of teaching tactics of using physical force and combat techniques by police officers. Results and conclusions. The authors consider the main scientific and methodological aspects of teaching tactics for the use of physical force and combat techniques by police officers in conditions close to operational activities. The leading pedagogical condition for training is the inclusion in the learning process of not only mastering the technical basics of combat techniques, but also tactical ones, which makes it possible to build the process of mastering educational material in a practice-oriented manner and, accordingly, more effectively.